RETRACTED: Peran Modal Sosial Terhadap Perkembangan Terhadap Pedagang Kaki Lima Dalam Persfektif Ekonomi Islam ( Studi Pasar Metau Muara Beliti Kecamatan Muara Beliti Kabupaten Musi Rawas Provinsi Sumatera Selatan) - Andrea Desta Rusnila; Idwal B; Nonie Afrianty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
RETRACTED NOTICE Following up on the review of articles published in the Ekombis Review Journal carefully, carefully, and thoughtfully, the article entitled "The Role of Social Capital on the Development of Street Vendors in the Islamic Economic Perspective (Study of Muara Beliti Metau Market, Muara Beliti District, Musi Rawas Regency, South Sumatra Province)". Vol 11 No 2 (2023): , DOI: https://doi.org/10.37676/ekombis.v11i2.4071 This paper is at the request of the author, withdrawn with the reasons attached to the attached article retraction letter in PDF form. The document and its contents have been removed from the Ekombis Review Journal, and reasonable efforts should be made to remove all references to this article.